DATA ANALYSIS AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF BACTERIAL PATHOGENS CAUSING URINARY TRACT INFECTION - Dr Narendra Mandoria, Dr K. Dashora, Dr Praveen Khirwadkar; Urmila Rathore; Govind Kirar; Dr Tanu Bhargava (Journal of Medical Care Research and Review, 2023)
Urinary tract infection (UTI) is the commonest bacterial infectious disease in community practice with a high rate of morbidity and financial cost. It has been estimated that 150 million people were infected with UTI per annum worldwide which costing global economy more than 6 billion US dollars [1]. UTIs is described as a bacteriuria with urinary symptoms [2]. UTI can affect lower and sometimes both lower and upper urinary tracts. The term cystitis has been used to define the lower UTI infection and is characterized by symp- toms such as dysuria, frequency, urgency, and suprapubic tenderness. The presence of the lower UTI symptoms does not exclude the upper UTI which is often present in most UTI cases [3]. The treatment of UTI can be classified into uncomplicated and complicated on the basis of their choice of treatment [4]. UTI is more common in females than in males as female urethra structurally found less effective for preventing the bacterial entry [5]. It may be due to the proximity of the genital tract and urethra [6] and adherence of urothelial mucosa to the mucopolysaccharide lining [7]